2022
DOI: 10.1002/mp.15510
|View full text |Cite
|
Sign up to set email alerts
|

Time‐resolved MRI for off‐line treatment robustness evaluation in carbon‐ion radiotherapy of pancreatic cancer

Abstract: In this study, we investigate the use of magnetic resonance imaging (MRI) for the clinical evaluation of gating treatment robustness in carbonion radiotherapy (CIRT) of pancreatic cancer. Indeed, MRI allows radiation-free repeated scans and fast dynamic sequences for time-resolved (TR) imaging (cine-MRI), providing information on inter-and intra-fraction cycle-to-cycle variations of respiratory motion. MRI can therefore support treatment planning and verification, overcoming the limitations of the current clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Data analysis was ongoing at the time of writing. As part of the study, our group critically analysed the challenges of organ motion management [67] including using MRI [68].…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…Data analysis was ongoing at the time of writing. As part of the study, our group critically analysed the challenges of organ motion management [67] including using MRI [68].…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…Ultimately, with fast time-resolved synthetic 4D-CT generation methods, dose calculation, and optimization algorithms, the partially delivered dose could be reconstructed and accumulated in real-time during the treatment fraction itself, and the treatment plan could be continuously adapted based on this information (Kontaxis et al 2015, Menten et al 2017. Further applications of such time-resolved synthetic 4D-CTs include gating window optimization (Oh et al 2019), 4D and robust treatment plan optimization and analysis (Heath et al 2009, Meschini et al 2022, and the investigation of interplay effects (Rao et al 2012, von Münchow et al 2022. Furthermore, the dose reconstructed over the whole treatment course could serve as input for clinical dose-response modeling in the post-treatment phase (van Herk et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the propagation method to create estimated 4D-MRI datasets has been adapted for use at a MRIdian MR-linac by Rabe et al (2021) and experimentally validated with a porcine lung phantom, which showed that the 3D anatomy in the whole phantom thorax could be estimated with high accuracy. Recently, the method has been extended by Meschini et al (2022) to create time-resolved virtual CTs based on a 3D-CT dataset and orthogonal cine MRI data acquired at a 3.0 T diagnostic scanner for offline treatment robustness evaluation in carbon-ion radiotherapy of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing use of magnetic resonance imaging (MRI) in photon radiotherapy to guide treatment is rapidly translating also into PT, with some feasibility studies on integrating in-room MRI with a proton beam (Hoffmann et al 2020), and others demonstrating the potential of offline MRI in supporting treatment planning (Meschini et al 2022b). Specifically for moving organs, the radiation-free modality combined with fast dynamic sequences allows for long and repeated acquisitions (Jaffray 2012, Paganelli et al 2018b, Keall et al 2022 to derive respiratory-correlated 4D magnetic resonance imaging (4DMRI) accounting for respiratory motion variability (Fontana et al 2016, Stemkens et al 2018, Paganelli et al 2018b, Paganelli et al 2019.…”
Section: Introductionmentioning
confidence: 99%